The use of virtual reality in studying prejudice and its reduction: A systematic review. - Matilde Tassinari; Matthias Burkard Aulbach; Inga Jasinskaja-Lahti (PLoS ONE, 2022)
This systematic review provides an up-to-date analysis of existing literature about Virtual Reality (VR) and prejudice. How has VR been used in studying intergroup attitudes, bias and prejudice, are VR interventions effective at reducing prejudice, and what methodological advantages and limitations does VR provide compared to traditional methods are the questions we aim to answer. The included studies had to use VR to create an interaction with one or more avatars belonging to an outgroup, and/or embodiment in an outgroup member; furthermore, they had to be quantitative and peer-reviewed. The review of the 64 included studies shows the potential of VR contact to improve intergroup relations. Nevertheless, the results suggest that under certain circumstances VR contact can increase prejudice as well. We discuss these results in relation to the intergroup perspective (i.e., minority or majority) and target minority groups used in the studies. An analysis of potential mediators and moderators is also carried out. We then identify and address the most pressing theoretical and methodological issues concerning VR as a method to reduce prejudice.